Moderating Influence of Training and Development on Entrepreneurial Performance - Kowo, Solomon Akpoviroro; Akinbola, Olufemi Amos; Sabitu, Olalekan Owotutu (Applied Studies in Agribusiness and Commerce, 2018)
This study assessed the moderating effect of training and development on entrepreneurial performance of Micro, Small and Medium Enterprises (MSMEs) in Nigeria considering the Bank of Industry and Small and Medium Enterprises Development Agency of Nigeria (SMEDAN). Two hypotheses were tested in this study reflecting training and development in Nigeria and Ethical practices of Training and Development impacts on behavioral outcomes of entrepreneurs. The paper puts to test, the preceding assertions with the aid of Kruskal Wallis test. From the test, the study refutes the former assertions on the reasoning that P-values were less than 5% level of significance. This showed that the impact of ethical training and development would be more significant if the young entrepreneurs had earlier exposure from secondary to tertiary education level to make better entrepreneurs in Nigeria. The study observed that the Nigerian educational system has contributed positively to the area of training and development which has enhanced entrepreneurial performance in Nigeria. The study recommends that training and development programme should focus on developing creative or innovative individuals who can help to move the nation forward. A Self-reliant person is a creative individual. JEL Classification: M53, M1